2010
DOI: 10.1080/09658211.2010.506441
|View full text |Cite
|
Sign up to set email alerts
|

Metacomprehension judgements reflect the belief that diagrams improve learning from text

Abstract: In two experiments we systematically explored whether people consider the format of text materials when judging their text learning, and whether doing so might inappropriately bias their judgements. Participants studied either text with diagrams (multimedia) or text alone and made both per-paragraph judgements and global judgements of their text learning. In Experiment 1 they judged their learning to be better for text with diagrams than for text alone. In that study, however, test performance was greater for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
93
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 31 publications
10
93
2
1
Order By: Relevance
“…Furthermore, students often believe that they learn more from multimedia materials than from text alone, regardless of whether or not this is the case (Serra & Dunlosky, 2010). In parallel to our findings, Serra and Dunlosky (2010) found that students accurately predicted that diagrams would improve their text comprehension; however, they inaccurately predicted that irrelevant illustrations would also improve their text comprehension. These authors attributed students' predictions to a general, undifferentiated belief about multimedia learning, namely, that visuals always help.…”
Section: Relations Between Problem-solving Performance and Problem Evsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, students often believe that they learn more from multimedia materials than from text alone, regardless of whether or not this is the case (Serra & Dunlosky, 2010). In parallel to our findings, Serra and Dunlosky (2010) found that students accurately predicted that diagrams would improve their text comprehension; however, they inaccurately predicted that irrelevant illustrations would also improve their text comprehension. These authors attributed students' predictions to a general, undifferentiated belief about multimedia learning, namely, that visuals always help.…”
Section: Relations Between Problem-solving Performance and Problem Evsupporting
confidence: 75%
“…Students often have misconceptions about their own learning (Bjork, Dunlosky, & Kornell, 2013). Furthermore, students often believe that they learn more from multimedia materials than from text alone, regardless of whether or not this is the case (Serra & Dunlosky, 2010). In parallel to our findings, Serra and Dunlosky (2010) found that students accurately predicted that diagrams would improve their text comprehension; however, they inaccurately predicted that irrelevant illustrations would also improve their text comprehension.…”
Section: Relations Between Problem-solving Performance and Problem Evsupporting
confidence: 74%
“…However, given the belief that a multimedia presentation of material is more comprehensible than a textonly presentation (Serra & Dunlosky, 2010), it is possible that the multimedia format could explain the higher metacomprehension judgment under the brain image condition. Therefore, in Experiment 2, we investigated whether a difference in the format of a diagram (i.e., brain image vs. bar graph) affects metacomprehension judgment.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, belief about multimedia presentations-that is, the belief that illustrated text is understood better than nonillustrated text-affects metacomprehension judgment. Serra and Dunlosky (2010) demonstrated that readers who read text accompanied by conceptual diagrams or photographs judged their level of comprehension as higher than did those who read text only, reflecting a multimedia belief among the participants. However, performance on the comprehension test was higher for text accompanied by conceptual diagrams than for text only and text accompanied by photographs.…”
mentioning
confidence: 99%
“…Seeing and hearing the pronunciation rules in blocked fashion may have rendered them easier to notice than seeing and hearing them in interleaved fashion. In previous studies, participants have reported that they learned material better when it was presented in a fashion that was designed to increase its ease or fluency of encoding, such as increasing the font size of text (e.g., Rhodes & Castel, 2008), increasing the coherency of text (e.g., Rawson & Dunlosky, 2002), or providing pictures with text (e.g., Carpenter & Olson, 2012;Serra & Dunlosky, 2010).…”
Section: Discussionmentioning
confidence: 99%